The Oxford handbook on the greening of economic development - Mathews, John A.; Oqubay, Arkebe (New York : Oxford University Press, 2025)
"Economic development, in its traditional formulation, ignores the impact of choices made regarding energy, resources, and finance. The standard choices made are to use stocks of fossil fuels and resources and their linear flow, and generic finance. The implications of these choices are now clear. An alternative is being crafted based on flows of renewable energy and renewable fuels, circular flows of resources, and greening of financial instruments such as equities and bonds. This involves a vast industrial revolution, creating the 'next' Great Transformation of the global economic system, one that is creating an economy that emulates life through its interconnections and circular flows. The shift is comprehensive, global, and all-encompassing. Greening of economic development is driven by industrial policy, technological capability, and enhancement of industrial capacity. This Handbook draws on specialist expertise to provide a comprehensive overview of this process of greening of economic development. It demonstrates how the shift in energy, resource flows, and finance is a process rather than an endpoint; that it is compatible with economic growth; driven by economic drivers such as cost reductions generated by experience curves; and at the vast scale and rapid pace required calls for a global Green Deal. The Handbook appeals to business and government policymakers in framing novel objectives through greening that take state action and guidance in fresh directions. The strategies are as relevant for emerging industrial economies leapfrogging to advanced technologies as to developed economies looking to transform themselves. Greening creates an affordable self-sustaining economy"--